Identity : the demand for dignity and the politics of resentment - Fukuyama, Francis (New York : Farrar, Straus and Giroux, 2018)
"In 2014, Francis Fukuyama wrote that American institutions were in decay, as the state was progressively captured by powerful interest groups. Two years later, his predictions were borne out by the rise to power of a series of political outsiders whose economic nationalism and authoritarian tendencies threatened to destabilize the entire international order. These populist nationalists seek direct charismatic connection to "the people," who are usually defined in narrow identity terms that offer an irresistible call to an in-group and exclude large parts of the population as a whole"--Provided by publisher.
Includes bibliographical references (p. 185-203) and index.
Booklist
New York Times
Publishers Weekly
Booklist, August 2018
Kirkus Review, June 2018
Keywords: Dignity; Group identity -- Political aspects; Identity politics; Polarization (Social sciences) -- Political aspects; Political participation -- Social aspects; Resentment; World politics -- 21st century; Group identity -- Political aspects; Political participation -- Social aspects; Values; World politics